Keberadaan Manusia dari Perspektif Roma 7:14: Sebuah Studi Antropologis-Teologis - Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Abstract: Anthropology is a study of how humans understand and evaluate various aspects of life. From a Christian perspective, anthropology needs to be seen from the standpoint of the Bible. The intersection between the science of anthropology and theology is evident in the writings of Paul. Paul elucidates the anthropological aspect in his letter to the Romans. Romans 7:14 is a rather challenging verse, and it explicates about humans. Humans experience tension between their old human life and their new life resulting from Christ's sacrifice in response to the Law of Moses. Although the Law of Moses is spiritual, humans are entrenched in the existence of sin, causing them to fail to obey the Law of Moses perfectly. Jesus is the divine human who can perfectly obey all the demands of the Law of Moses. Through a descriptive qualitative approach, it can be concluded that human anthropology from the perspective of Romans 7:14 leads humans to place their faith in Jesus Christ.Abstrak: Antropologi adalah sebuah studi tentang bagaimana manusia memahami dan menilai berbagai aspek kehidupan. Dalam perspektif Kristianitas, antropologi perlu dilihat dari sisi Alkitab. Persinggungan antara ilmu antropologi dan juga ilmu teologi terlihat jelas dalam tulisan Paulus. Paulus menjelaskan sisi antropologi dalam tulisannya kepada jemaat di Roma. Roma 7:14 adalah ayat yang cukup sukar dan ayat tersebut menjelaskan tentang manusia. Manusia memiliki ketegangan antara kehidupan lama manusia dan juga kehidupan manusia yang baru akibat dari pengorbanan Kristus dalam merespon Hukum Taurat. Meskipun Hukum Taurat bersifat rohani, namun manusia ada di dalam keberadaan dosa yang membuat manusia gagal mentaati Hukum Taurat secara sempurna. Yesus adalah manusia illahi yang dapat mentaati segala tuntutan Hukum Taurat secara sempurna. Melalui pendekatan kualitatif deskriptif, dapat disimpulkan bahwa antropologi manusia dalam perspektif Roma 7:14 membawa manusia untuk menaruh iman di dalam Yesus Kristus.